Chemical and DPPH Free Radical Scavenging Stability of Avocado Seed Acetone Extract Against pH Changes - Suradnyana, I Gede Made; Juliadi, Debby; Mendra, Ni Nyoman Yudianti; Suena, Ni Made Dharma Shantini (Jurnal Ilmiah Medicamento, 2026)
Background: Avocado seeds contain phenol, flavonoid, and anthocyanidin compounds that have antioxidant activity. The stability of phenolic compounds depends on the pH of the solution. A decrease in total phenolic levels causes a decrease in antioxidant activity. The chemical stability and DPPH free radical scavenging activity of avocado seed extract against pH are not yet known. Objective: This study aimed to determine the effect of pH on the chemical stability and DPPH free radical scavenging activity of avocado seed extract. Methods: Chemical stability was observed from changes in total phenolic levels, and stability of DPPH free radical scavenging activity was observed from the difference in the percentage of DPPH reduction of the extract solution in phosphate-citrate buffer at pH 3.24, 5.52, and 7.44 before and after being heated at 60°C for 2 hours. Results: The average decrease in total phenolic levels of the extract in buffer pH 3.24, 5.52, and 7.44 before and after being heated was 5.76%, 3.89%, and 22.08%, respectively. The decrease in DPPH free radical scavenging activity of the extract in buffer pH 3.24, 5.52, and 7.44 before and after heating was 24.78%, 1.96%, and 56.09%, respectively. There is a significant difference in the total phenolic content and DPPH free radical scavenging activity of the acetone extract solution in phosphate–citrate buffer at pH 3.24 and 7.44 before and after heating, but there is no significant difference at pH 5.52. Conclusion: Therefore, in the development of formulations containing acetone extract of avocado seeds, buffering at a pH close to 5.22 is required.